Effects of feeding increasing levels of yerba mate on lamb meat quality and antioxidant activity - Pena-Bermudez, Yuli A.; Lobo, Richard R.; Rojas-Moreno, Danny A.; Poleti, Mirele D.; de Amorim, Tamyres R.; Rosa, Alessandra F.; Pereira, Angélica S. C.; Pinheiro, Rafael S. B. [UNESP]; Bueno, Ives C. S. (MDPI, 2020)
The present study investigated the inclusion of yerba mate extract (YME) in the lamb’s diet on meat quality traits, antioxidant activity, and shelf-life. Thirty–six lambs were distributed according to a block design with the following groups: control group without YME (0%) and three treatment groups with 1, 2, and 4% YME inclusion in the dry matter. The animals were fed these diets for 53 days. Samples were collected from the Longissimus thoracis (LT) muscle to analyze antioxidant activity and meat quality. Samples were placed on a counter display simulating a retail environment for 0, 3, and 6 days at 4 ± 2◦C. All data were analyzed using a MIXED model with orthogonal contrasts. Inclusion of 1 and 4% YME in the diet changed the yellow (b*) and the chroma (C*) of the meat (p ≤ 0.05). The pH, colour, thiobarbituric acid reactive substances, and carbonyl values were influenced by the retail display time for all the evaluated treatments (p ≤ 0.03). However, neither diet nor the retail display time influenced the oxidation of proteins or the antioxidant enzyme activities of catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPX) and glutathione activity (GSH) in meat. Therefore, the inclusion of 4% YME showed positive results in the yellow and colour stability parameters of the meat without increasing the lipid peroxidation values or altering the normal meat quality parameters in lambs.
Keywords: Meat quality; Natural antioxidants; Oxidative stability; Polyphenolic; Useful life